NATO/KFOR na Kosovu - Hibšer, Krešimir (2004)
NATO/KFOR misija, u sklopu širih međunarodnih napora da se uspostavi mir na Kosovu, u prvih nekoliko godina dala je niz uspješnih, ali i neuspješnih rezultata, promatrano s aspekta Rezolucije 1244 Vijeća sigurnosti i nekoliko sigurnosnih aranžmana potpisanih između Sjevernoatlantskog saveza i lokalnih aktera. Međutim, dolazak NATO postrojbi na teritorij na kojem ih do tada nije bilo, može se promatrati i kao bitan uspjeh Sjevernoatlantske alijanse u vojnom i geostrateškom pogledu. In first few years, the NATO/KFOR joint mission within the framework of wider international efforts to establish peace in Kosovo accomplished a series of successful results, but it also had a number of setbacks, if we take into consideration the UN 1244 Resolution as well as other security arrangements concluded between NATO and local actors. However, the arrival of NATO troops onto the territory where they had never been deployed before can be considered as a significant success of the North-Atlantic Alliance, both in military and geostrategic terms.